Intracranial Pressure and Brain Monitoring XV - Ang, Beng-Ti (Acta neurochirurgica, 2016)
PART 1 Acute Brain Pathologies - Treatment and Outcome -- Mechanism of Traumatic Brain injury at distant locations after exposure to blast waves: Preliminary results from animal and phantom experiments -- Early Changes in Brain Oxygen Tension May Predict Outcome Following Severe Traumatic Brain Injury -- Attitudes in 2013 to Monitoring Intracranial Pressure Monitoring for Traumatic Intracerebral Haemorrhage -- Topical therapy following an acute experimental head injury with mesenchymal stem cells (MSCs) has benefits in motor-behavioural tests for rodents -- Drag Reducing Polymer Enhances Microvascular Perfusion in the Traumatized Brain with Intracranial Hypertension -- PART 2 Clinical Monitoring of Intracranial Pressure -- Continuous Monitoring of the Complexity of Intracranial Pressure after Head Injury -- Characterization of Supra and Infra-Tentorial ICP Profiles -- Multi-resolution convolution methodology for ICP waveform morphology analysis -- Evaluation of Intracranial Pressure in Different Body Postures and Disease Entities -- Identification of clinically relevant groups of patients through the application of cluster analysis to a complex traumatic brain injury data set -- CSF lumbar drainage: a safe surgical option in refractory intracranial hypertension associated with acute post-traumatic external hydrocephalus -- Intracranial Pressure Waveforms are More Closely Related to Central Aortic than Radial Pressure Waveforms: Implications to Pathophysiology and Therapy -- Noninvasive Intracranial Pressure Determination in Patients with Subarachnoid Hemorrhage -- Non-Invasive Assessment of ICP – Evaluation on new TBI Data Material -- Real-Time Processing of Continuous Physiological Signals in a Neurocritical Care Unit on a Stream Data Analytics Platform -- The correlation between intracranial pressure and cerebral blood flow velocity during ICP plateau waves -- Outcome Prediction for Traumatic Brain Injury Patients with Dynamic Features from Intracranial Pressure and Arterial Blood Pressure Signals: A Gaussian Process Approach -- Validation of a new noninvasive intracranial pressure monitoring method by direct comparison with an invasive technique -- Validation of a new minimally invasive intracranial pressure monitoring method by direct comparison with an invasive technique -- Monitoring of Intracranial Pressure in Meningitis PART3 Special Topics in Intracranial Pressure Science -- Bernoulli’s Principle Applied To Brain’s Fluids: Intracranial Pressure Does Not Drive Cerebral Perfusion Or CSF Flow -- ‘Solid red line’-an observational study on death from refractory intracranial hypertension -- Patient-Specific Thresholds and Doses of Intracranial Hypertension in Severe Traumatic Brain Injury -- Characterization of ICP behavior in an experimental model of hemorrhagic stroke in rats -- Intrahospital transfer of patients with traumatic brain injury: increase of intracranial pressure -- Early cognitive domain deficits in patients with aneurysmal subarachnoid hemorrhage are correlated with functional status -- Brain Oxygen Relationship to Cerebral Perfusion Pressure Depends on Tip Location and Time Window: Can Brain O2 be an adjunctive modality for determining optimal CPP? -- The interaction between heart systole and cerebral circulation during lower body negative pressure test -- Plateau Waves of Intracranial Pressure and Multimodal Brain Monitoring -- The diastolic closing margin is associated with intraventricular hemorrhage in premature infants -- The ontogeny of cerebrovascular pressure autoregulation in premature infants -- Finite Element Model for Hydrocephalus and Idiopathic Intracranial Hypertension -- External ventricular catheter placement: How to improve -- PART4 Autoregulation and Experimental Studies in Brain Injury -- Change in Pulsatile Cerebral Arterial Pressure and Flow Waves as a Therapeutic Strategy?- Increasing intracranial pressure after head injury: Impact on respiratory oscillations in cerebral blood flow velocity -- Plateau Waves of Intracranial Pressure and Partial Pressure of Cerebral Oxygen -- Is impaired autoregulation associated with mortality in patients with severe cerebral diseases? -- Continuous optimal CPP based on minute-by-minute monitoring data: a study on a pediatric population -- Effects of brain temperature on cerebrovascular autoregulation during the acute stage of severe traumatic brain injury -- Monitoring cerebral autoregulation after subarachnoid hemorrhage -- Correlation between cerebral autoregulation and carbon dioxide reactivity on patients with traumatic brain injury -- Cerebral arterial time constant recorded from MCA and PICA in normal subjects -- Cerebral Critical Closing Pressure during Infusion Tests -- Outcome, Pressure Reactivity and Optimal Cerebral Perfusion Pressure Calculation in Traumatic Brain Injury: A Comparison of two Variants -- Identification of an Intracranial Pressure Response Function from Continuously Acquired Electroencephalographic and Intracranial Pressure Signals in Burst-Suppressed Patients -- The upper limit of cerebral blood flow autoregulation is decreased with elevations in intracranial pressure -- Derangement of cerebral blood flow autoregulation during intracranial pressure plateau waves as detected by time and frequency based methods -- State of Cerebrovascular Autoregulation Correlates To Outcome In Severe Infant/Pediatric Traumatic Brain Injury -- Can optimal cerebral perfusion pressure in severe traumatic brain injury patients be calculated based on minute-by-minute monitoring data? -- The ontogeny of cerebrovascular critical closing pressure -- Dynamic Cerebrovascular and Intracranial Pressure Reactivity Assessment of Impaired Cerebrovascular Autoregulation in Intracranial Hypertension -- PART 5 Biophysics and Experimental Aspects of Intracranial Pressure -- Automatic Calculation of Hydrostatic Pressure Gradient in Head Injured Patients: A Pilot Study -- The prediction of shunt response in idiopathic normal pressure hydrocephalus based on intracranial pressure monitoring and lumbar infusion -- Intracranial hypertension is painless! -- The effect of body position on intraocular and intracranial pressures in rabbits -- Monoamine neurotransmitter metabolites concentration as a marker of cerebrospinal fluid volume changes -- Disproportionately enlarged subarachnoid-space hydrocephalus in idiopathic normal pressure hydrocephalus and its implication in pathogenesis -- Characterization of Cerebral Vascular Response to EEG Bursts Using ICP Pulse Waveform Template Matching -- Tranc-ependimal movement of cerebro-spinal fluid in neurologic and psychiatric pathologies -- Artifact in physiological data collected from brain injured patients: quantifying the problem and providing a solution through a factorial switching linear dynamical systems approach -- Central Pulsatile Pressure and Flow Relationship in Time and Frequency Domain to Characterise Hydraulic Input to the Brain and Cerebral Vascular Impedance -- Reproduction of ICP Waveform Changes in a Mathematical Model of the Cerebrospinal Circulatory System -- Accuracy, precision, sensitivity and specificity of non-invasive ICP absolute value measurements -- Measurement of intraspinal pressure after spinal cord injury: technical note from the Injured Spinal Cord Pressure Evaluation Study -- Characterization of the Intracranial Pressure Behavior in Chronic Epileptic Animals: a Preliminary Study -- Waveform Analysis of Intra Spinal Pressure after Traumatic Spinal Cord Injury- an Observational Study (O-64) -- Relative Position of the Third Characteristic Peak of the Intracranial Pressure Pulse Waveform Morphology Differentiates Normal Pressure Hydrocephalus Shunt Responders and Non-Responders -- Who needs a revision? 20 years of Cambridge Shunt Lab (O-69) -- Shunt testing in-vivo: problems with ventricular catheter- observational study. (O-70) -- NPH Case Report: A Documented Self Story over Eight Years with my Observations.
Keywords: Konferenzschrift; Patientenüberwachung; Hirndruck; Schädel-Hirn-Trauma